Evidence for Solar Modulation on the Millennial-Scale Climate Change of Earth - Xinhua Zhao; Willie Soon; Victor M. Velasco Herrera (Universe, 2020)
In this study, we use available reconstructed data to investigate periodicities of solar activity (i.e., sunspot number) and the Earth’s climate change (temperatures of Lake Qinghai in China and Vostok in Antarctica, the GISP δ18O climate record of Greenland, and the stalagmite δ18O monsoon records of Dongge Cave in China) as well as their cross-wavelet coherences on millennial scale. We find that the variations of the Earth’s climate indices exhibited the 1000-year cyclicity, which was recently discovered in solar activity (called Eddy cycle). The cross-wavelet correlations between the millennium-cycle components of sunspot number and the Earth’s climate change remains both strong and stable during the past 8640 years (BC 6755–AD 1885). The millennial variation of sunspot number keeps in-phase with variations of Lake Qinghai temperature, Greenland temperature, and East Asian Monsoon, but anti-phase with the variation of Antarctica temperature. The strong and stable resonant relationships between sunspot numbers and these climate indices indicate that solar variability may have played a role in modulation on this millennial seesaw pattern of the Earth’s climate change before the modern industrial era.